The Effect of Sports Attitude on Healthy Lifestyle Behavior in University Students - Yalcin, Ilimdar; Yildirim Araz, Gamze; Ekinci, Nurullah Emir; Birkok, Mehmet Cuneyt (Progress in Nutrition, 2020)
Study Objectives: In this study, it was aimed to determine the effect of university students’ sports attitudes on healthy lifestyle behavior and to examine the relationship between these two variables. Methods: A total of 749 students who studied in different departments at Bingöl University during the 2019-2020 academic year participated in the study as volunteers (Age: 21.71±2.20). In the research, besides the personal information form, "Healthy Lifestyle Behaviors Scale-II" and "Sports Attitude Scale" were used. In the analysis of the obtained data, Pearson Correlation and Linear Regression analysis were applied using the SPSS package program. Results: It was determined that there was a moderate positive relationship between the sports attitude and healthy lifestyle behavior in university students. In addition, it was determined that sports attitude predicted the healthy lifestyle behavior variable by 18%. Conclusion: It was seen that students’ sports attitudes had a positive effect on healthy lifestyle behaviors. This result shows that students have information about the important roles of sports in health (motivation, stress management, coping with depression, physical ability, regular eating habits, etc.).